On maximum packings of λ-fold complete 3-uniform hypergraphs with triple-hyperstars of size 4 - Amber Armstrong; Ryan C. Bunge; William Duncan; Saad I. El-Zanati; Kristin Koe; Rachel Stutzman (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2021)
A symmetric triple-hyperstar is a connected, 3-uniform hypergraph where, for some edge a, b, c, vertices a, b, and c all have degree k > 1 and all other edges contain exactly 2 vertices of degree 1. Let H denote the symmetric triple-hyperstar with 4 edges and, for positive integers λ and v, let λKv(3) denote the λ-fold complete 3-uniform hypergraph on v vertices. We find maximum packings of λKv(3) with copies of H.